Vergleich von 201T1 und 99mTc-MIBI in der Nachsorge des differenzierten Schilddrüsenkarzinoms - Briele, B.; Hotze, A.; Kropp, J.; Bockisch, A.; Overbeck, B.; Grünwald, F.; Kaiser, W.; Biersack, H. J. (Nuklearmedizin - NuclearMedicine, 1991)
12 patients with suspected recurrence of differentiated thyroid carcinoma following thyroidectomy, radioiodine therapy and, in some cases, external radiation therapy had 201T1 and 99mTc-MIBI scintigraphy. Except in one case, the findings concerning tumor localization and extension were identical. In all cases, locoregional lymph node metastases as well as osseous metastases were imaged by 201T1 and 99mTc-MIBI scintigraphy. MRI images obtained in all patients with suspected lymph node metastases revealed inoperable situations in 2 cases, whereas there was no correlation in patient with positive 201T1 and 99mTc-MIBI scintigraphy. In contrast, the sensitivity of the two methods was relatively low in the detection of pulmonary metastases which were imaged in 1 out of 3 patients only. Discrepancies between 201T1 and 99mTc-MIBI were observed in a case of axillary lymph node metastasis. Although tumor-/background ratios were slightly higher for 201T1, 99mTc-MIBI SPECT showed a higher imaging quality compared to 201T1 SPECT, especially in deeply situated tumor lesions. In conclusion, 99mTc-MIBI seems to be a promising alternative imaging agent in the follow-up of differentiated thyroid carcinomas.